A population-specific HTR2B stop codon predisposes to severe impulsivity - Bevilacqua, Laura; Doly, Stéphane; Kaprio, Jaakko; Yuan, Qiaoping; Tikkanen, Roope; Paunio, Tiina; Zhou, Zhifeng; Wedenoja, Juho; Maroteaux, Luc; Diaz, Silvina; Belmer, Arnaud; Hodgkinson, Colin A.; et al. (Nature (London), 2010)
Impulsivity, describing action without foresight, is an important feature of several psychiatric diseases, suicidality and violent behaviour. The complex origins of impulsivity hinder identification of the genes influencing it and the diseases with which it is associated. Here we perform exon-focused sequencing of impulsive individuals in a founder population, targeting fourteen genes belonging to the serotonin and dopamine domain. A stop codon in HTR2B was identified that is common (minor allele frequency > 1%) but exclusive to Finnish people. Expression of the gene in the human brain was assessed, as well as the molecular functionality of the stop codon, which was associated with psychiatric diseases marked by impulsivity in both population and family-based analyses. Knockout of Htr2b increased impulsive behaviours in mice, indicative of predictive validity. Our study shows the potential for identifying and tracing effects of rare alleles in complex behavioural phenotypes using founder populations, and indicates a role for HTR2B in impulsivity. A genetic link to impulsion Impulsive behaviour — action taken without foresight — is a feature of several psychiatric disorders, some of which have been shown to be moderately heritable. In a search for a genetic signature for that heritability, exon sequencing focusing on 14 serotonin and dopamine-related genes in severely impulsive Finnish criminal offenders reveals linkage to a mutation in the stop codon HTR2B . The gene, which encodes the 5HT 2B serotonin receptor, was not previously known to influence behaviour. The role of this serotonin receptor in impulsivity is further supported by the knockout mouse phenotype. Impulsive behaviour characterizes several psychiatric diseases and violent behaviour but its origins are complex. Here, exon sequencing focused on fourteen serotonin- and dopamine-related genes identified a mutation in HTR2B , which was associated with psychiatric diseases marked by impulsivity in a Finnish population. The role of this serotonin receptor in impulsivity is further supported by the knockout mouse phenotype.